Preliminary Examination of the Impact of Program Factors on Summary Effect Sizes - Taylor, Liana R. (International journal of offender therapy and comparative criminology, 2021)
The Washington State Institute for Public Policy (WSIPP) uses meta-analyses to help program administrators identify effective programs that reduce recidivism. The results are displayed as summary effect sizes. Yet, many programs are grouped within a category (such as Intensive Supervision or Correctional Education), even though the features of the programs might suggest they may be very different. The following research question was examined: What program features are related to the effect size in the WSIPP program category? Researchers at ACE! at George Mason University reviewed the studies analyzed by WSIPP and their effect sizes. The meta-regression global models showed recidivism decreased with certain program features, while other program features actually increased recidivism. A multivariate meta-regression showed substantial variation across Cognitive-Behavioral Therapy programs. These preliminary findings suggest the need to further research how differing program features contribute to client-level outcomes, and develop a scheme to better classify programs.